Intestinal Microbial and Metabolic Alterations Following Successful Fecal Microbiota Transplant for D-Lactic Acidosis. Issue 4 (October 2018) - Bulik-Sullivan, Emily C.; Roy, Sayanty; Elliott, Ryan J.; Kassam, Zain; Lichtman, Steven N.; Carroll, Ian M.; Gulati, Ajay S.
Abstract : ABSTRACT: Fecal microbiota transplantation (FMT) involves the transfer of stool from a healthy individual into the intestinal tract of a diseased recipient. Although used primarily for recurrent Clostridium difficile infection, FMT is increasingly being attempted as an experimental therapy for other illnesses, including metabolic disorders. D-lactic acidosis (D-LA) is a metabolic disorder that may occur in individuals with short bowel syndrome when lactate-producing bacteria in the colon overproduce D-lactate. This results in elevated systemic levels of D-lactate, metabolic acidosis, and encephalopathy. In this study, we report the successful use of FMT for the treatment of recurrent D-LA in a child who was unresponsive to conventional therapies. Importantly, we also present profiles of the enteric microbiota, as well as fecal D-/L-lactic acid metabolites, before and longitudinally after FMT. These data provide valuable insight into the putative mechanisms of D-LA pathogenesis and its treatment. Abstract : Supplemental Digital Content is available in the text